Structure of a general solution of systems of nonlinear difference equations - Pelyukh, G. P.; Пелюх, Г. П.; Пелюх, Г. П. (Institute of Mathematics, NAS of Ukraine, 1999)
We investigate the structure of a general solution of systems of nonlinear difference equations with continuous argument in a neighborhood of the state of equilibrium.